Formation of the integrated innovative infrastructure of the Eurasian economic union as a factor of increase in knowledge intensity of economies of member countries - Shelomentsev, A.; Taubayev, A.; Amirova, G.; Kasymova, N. (BUKETOV BUSINESS REVIEW, 2019)
In the article the creation of the integrated innovative infrastructure did not lead development of integration within the Eurasian Economic Union to noticeable increase in knowledge intensity of GDP. The short period of existence of the Eurasian Economic Union and shorter period of functioning of the integrated innovative infrastructure did not lead to noticeable activation of the hi-tech sector in economies of member countries. Low level of knowledge intensity of GDP is characteristic sign for all countries of EAEU, except Russia that demands development of more detailed and financially secured programs of increase in knowledge intensity in member countries. The results of the research will be interesting to appropriate authorities of public administration of the member countries of EAEU, supranational structures of the Eurasian economic commission dealing with the issues of formation of innovative infrastructure and development of the hi-tech sector and also the scientists dealing with issues of development of science and an innovation in integration regional associations. On the basis of the received results it is necessary to correct national innovative policies of member countries of EAEU and actions for strengthening of integration in the direction of scientific and technical cooperation within EAEU. The empirical analysis was carried out on the basis of gaps in the researches connected with support of scientific and technical cooperation within EAEU.